Application of mobile reality in the training of health sciences students - García-Huamantumba, Elvira (2024)
Introduction: education in the 21st century has undergone a profound transformation thanks to technological advances. In this context, augmented reality (AR) has emerged as an innovative pedagogical tool that promises to revolutionize the way students acquire knowledge and skills. Objective: establish the impact of augmented reality on the learning of health sciences students at a private university in Lima. Methods: it is a quantitative, descriptive, non-experimental, cross-sectional study, whose sample was 74 health sciences students from a private university in Lima. The survey technique was used and the instrument was the questionnaire. Results: the use of AR was located at an intermediate level with 43,24 % (32), in learning, a medium level was recorded in 40,54 % (30) of the participants; The same trend occurred in the dimensions of both variables. Conclusions: it was determined that AR has a significant impact on the learning process of health sciences students at a private university in Lima, demonstrated through the Chi-square analysis, p-value = 0,023 < 0,05.